Cognitive Counseling Behavioral with Modeling The Figure of Dharmawangsa to Increase Verbal - Wati, Ida Ayu Widya; Suarni, I Ketut; Dharsana, I Ketut (Department of Guidance and Counseling, FIP, Undiksha, 2017)
This research aims to know the influence of behavioral counselingModeling techniquesDharmawangsa figure to improve verbal through lesson study on grade XII HIGH SCHOOL Language Lab Undiksha.This type of research is Research experiment pseudo (